Introduction to English Vocabulary and Number Notation for Youth and Sunday School Children at HKBP Parmonangan - Samosir, Nelly Elisabeth; Banjarnahor, Elysta; Panggabean, Ance Juliet (Journal of Community Research and Service, 2023)
(Thematic Field Practice/PLT) is a required course for students of English Literature. This PLT implementation is a forum for each student to apply and improve the knowledge they have acquired in the fields of English Literature and Musical Arts in their community. In particular, through PLT he targets Sunday school children and youth in HKBP Parmonangan.This research can be classified as a type of descriptive research using qualitative methods, judging by the scope and results to be achieved. The survey was conducted with teenagers and Sunday school children from HKBP Parmonangan Church on Jl. Surya No. 12, Ex. IndraKasih Medan Tembung, North Sumatra. The activities of the author are as follows. (Thematic Field Practice/PLT) is a compulsory subject for students majoring in English Literature. The implementation of this PLT is a forum for all students to apply and enhance the knowledge gained in the field of English Literature to the community, especially Sunday School children at HKBP Parmonangan through the PLT. Based on the results of the discussion and on the data obtained from the actual work at the HKBP Parmonangan Church, the authors can make conclusions and recommendations that may be useful to all parties involved. deal with a problem, namely: Students learn more and can understand faster when they enter the world of work directly, Practical students acquire a wide range of knowledge in industrial practice, both theoretically and practically, Being able to know how to solve various problems directly, efficiently and effectively because they are linked to existing systems reduces errors and Can know how to work together between developers, distribution of tasks, means of communication and kinship created in PLT.